For the Poor, It was Just Friday: The Implicit Focus on Middle-class Habitus in Conceptualizing Disaster - Amy Sorensen; Shelley Koch (Critical Disaster Studies, 2022)
The importance of the academic study of disaster is in its potential application to policy and practice in times of dire circumstance and human suffering. In this paper, we situate the Covid-19 pandemic as an exemplar for an exploration of “disaster” using a framework that connects sociological theory and critical disaster studies. We use a Bourdieusian approach to situate the re-stabilization of the middle class habitus as implicitly central to disaster mitigation strategies. This theoretical approach illuminates the disconnect between critical disaster studies and on-the-ground disaster recovery approaches. It is this disconnect that leads to the disparate impact of disaster for the working and poverty classes. Through this analysis we suggest that policy-makers must engage with this discrepancy by shifting focus from the middle-class normative environment to the constant precarity of the working and poverty classes, either by centering them in disaster recovery policy or (preferably) by ameliorating the disaster-like conditions of the poverty class habitus overall.
Keywords: COVID-19; disaster; middle-class habitus; Bourdieu; disaster mitigation; poverty